Defense Strategy In Dealing With Threats Of National Security - M. Harlan Pariyatman; Adnan Madjid; Puguh Santoso; Pujo widodo; Herlina Saragih (CV. AFDIFAL MAJU BERKAH, 2023)
The national defense strategy is to prevent, deter and overcome threats and disturbances to the integrity of the nation and state in various forms by developing capabilities as the main component in the form of ready reinforcements and reserves so that they have high preparedness and immediate response. Indonesia's national defense is not carried out solely by military means, but is carried out based on three main pillars, namely the use of defense force, international cooperation and the development of defense forces even though Indonesia's national defense strategy does not adhere to the development of defense force facts. The purpose of this study is to determine the strength of the country's defense through the Indonesian National Armed Forces with the readiness of military operations other than war in the face of non-military threats. This study uses a descriptive qualitative research method with a literature study followed by data presentation, reduction and conclusion. The result of this research is that the state defense is carried out with several efforts such as forming a reserve component, establishing a universal people's security defense system, preparing an active defensive defense, and preparing a multi-layered defense.